2012
DOI: 10.1021/am300253c
|View full text |Cite
|
Sign up to set email alerts
|

Size-Dependent Cell Uptake of Protein-Coated Graphene Oxide Nanosheets

Abstract: As an emerging applied material, graphene has shown tremendous application potential in many fields, including biomedicine. However, the biological behavior of these nanosheets, especially their interactions with cells, is not well understood. Here, we report our findings about the cell surface adhesion, subcellular locations, and size-dependent uptake mechanisms of protein-coated graphene oxide nanosheets (PCGO). Small nanosheets enter cells mainly through clathrin-mediated endocytosis, and the increase of gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

24
305
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 341 publications
(331 citation statements)
references
References 33 publications
24
305
2
Order By: Relevance
“…GO has smoother edges and hydrophilic properties, and seems to be less potent in terms of penetrating cell compartments and interacting with DNA, resulting in the absence of genotoxic effects. Furthermore, it has been demonstrated that GO particles smaller than 500 nm may be internalized via clathrin-mediated 34 On the other hand, Yue et al 35 showed that 350 nm GO are wrapped by active filopodia of macrophages, while 2 µm GO enter cells nearly perpendicularly. This mechanism may trap GO inside vesicles, making it impossible for GO to penetrate into the nucleus and interact directly with DNA.…”
Section: Discussionmentioning
confidence: 99%
“…GO has smoother edges and hydrophilic properties, and seems to be less potent in terms of penetrating cell compartments and interacting with DNA, resulting in the absence of genotoxic effects. Furthermore, it has been demonstrated that GO particles smaller than 500 nm may be internalized via clathrin-mediated 34 On the other hand, Yue et al 35 showed that 350 nm GO are wrapped by active filopodia of macrophages, while 2 µm GO enter cells nearly perpendicularly. This mechanism may trap GO inside vesicles, making it impossible for GO to penetrate into the nucleus and interact directly with DNA.…”
Section: Discussionmentioning
confidence: 99%
“…However, the underlying mechanisms of cellular internalization of GBMs remain enigmatic and several pathways have been proposed. The two main working hypotheses include phagocytosis and clathrin-mediated endocytosis 30,31 but the possibility of membrane translocation through a "piercing effect" has also been revealed from computational studies 32,33 . Remarkably, photothermal effect due to the ability of graphene to absorb NIR light was suggested to enhance the transfection efficiency thanks to induced heating which locally disrupts the organization of the lipid bilayer cell membrane, hence rendering it more permeable and facilitating endosomal escape 34 .…”
Section: What Can Gbms Offer As Gene Delivery Platforms?mentioning
confidence: 99%
“…Almost no inhibition of cell proliferation was found at doses up to 100 µg/mL. 166 The in vitro hemocompatibility and genotoxicity of GO with human primary blood components remains a hotly …”
Section: Cytotoxicitymentioning
confidence: 99%